Do We Need a Regulation on Dividends for Indonesia Stock Exchange? - Leo Indra Wardhana; Eduardus Tandelilin (Gadjah Mada International Journal of Business, 2018)
This study examines the dividend life-cycle hypothesis and the propensity of non-financial firms listed on the Indonesia Stock Exchange (IDX) to pay dividends, in light of a recent idea by the IDX to regulate dividend payments. Using several proxies of the life cycle, the results consistently show that Indonesian listed firms follow the dividend life-cycle hypothesis. Our results recommend that if the authority insists on regulating dividend payments, the regulation should take into account the firms’ life cycles. Firms should only be required to pay dividends when they reach a certain stage and/or meet defined characteristics, according to their stage or characteristics.